Processing of Polypropylene-Organic Montmorillonite Nanocomposite by Equal Channel Multiangular Extrusion - V. A. Beloshenko; A. V. Voznyak; Yu. V. Voznyak; L. A. Novokshonova; V. G. Grinyov; V. G. Krasheninnikov (International Journal of Polymer Science)
By the example of polypropylene-organic montmorillonite composite (PP-OMMT), the abilities of the method of equal channel multiangular extrusion have been studied with respect to the modification of the structure and the properties of polymeric nanocomposites. With using X-ray structure analysis, TEM, DSC, and dilatometry, it has been demonstrated that this kind of processing provides an additional intercalation of the polymer into OMMT tactoids with the succeeding exfoliation and facilitates an increase in the aspect ratio, the degree of platelet orientation, the crystalline lamellar thickness, and a decrease in the dispersion of the crystallite thickness, as well as the formation of biaxial orientation of the OMMT and PP crystals. The observed structure rearrangements determine enhanced microhardness, ductility, and the heat distortion temperature of the PP-OMMT composite.